The present and future of digital sociology: An interview with Deborah Lupton - Lupton, Deborah; Fuentes, Anita; García Mingo, Elisa (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2023)
This article provides a reflection on digital sociology ten years into its development, including an interview with Deborah Lupton, one of the most prominent researchers in the field. In the interview, Lupton reflects on digital sociology from a current perspective, aware of the changes that this discipline has undergone since the publication of her work Digital sociology (2014). She talks about the new platforms, programs and digital devices that have become popular in recent years, and the effects of digital technologies on social research. Finally, she shares her thoughts on what the future of digital social research might look like, advocating for experimentation with creative methods and digital tools.